Building bridges rather than walls: research into an experiential model of interfaith education in secondary schools - McCowan, Tim (British journal of religious education, 2017)
This paper examines research findings from an experiential model of interfaith education called the Building Bridges through Interfaith Dialogue in Schools Programme (BBP). The BBP has been operating continuously in Melbourne, Australia since 2004. In the research, participating students were interviewed and surveyed to assess the effect of this experiential interfaith education programme on their knowledge, attitudes, perspectives and behaviour toward those from different religious and cultural backgrounds to them. Some of the data from those interviews are included in this article. The findings identify that the programme promoted religious literacy, (including improved knowledge, understanding and appreciation for different religious and cultural traditions and their practices), dismantled prejudice from ignorance and overly generalised stereotypes of others, and promoted social inclusion and cohesion.